2002
DOI: 10.1016/s0969-2126(02)00777-3
|View full text |Cite
|
Sign up to set email alerts
|

The Ig-like Structure of the C-Terminal Domain of Lamin A/C, Mutated in Muscular Dystrophies, Cardiomyopathy, and Partial Lipodystrophy

Abstract: Lamins are nuclear intermediate filaments that, together with lamin-associated proteins, maintain nuclear shape and provide a structural support for chromosomes and replicating DNA. We have determined the solution structure of the human lamin A/C C-terminal globular domain which contains specific mutations causing four different heritable diseases. This domain encompasses residues 430-545 and adopts an Ig-like fold of type s. We have also characterized by NMR and circular dichroism the structure and thermostab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
300
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(315 citation statements)
references
References 45 publications
10
300
0
5
Order By: Relevance
“…Less chromatin in regions of the nucleus could conceivably enhance exposure of the nucleoplasmic face of the inner nuclear membrane and thereby facilitate the egress of nucleocapsids. Since amino acids 411 to 553 of lamin A/C comprise a globular DNA binding domain that helps mediate association with chromatin (5,13,17,28,30), it was of interest that, through epitope mapping and GST pulldown reactions, we have determined that amino acids in or near the lamin A tail domain (amino acids 369 to 519 and 490 to 660) are sufficient to interact with U L 31 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Less chromatin in regions of the nucleus could conceivably enhance exposure of the nucleoplasmic face of the inner nuclear membrane and thereby facilitate the egress of nucleocapsids. Since amino acids 411 to 553 of lamin A/C comprise a globular DNA binding domain that helps mediate association with chromatin (5,13,17,28,30), it was of interest that, through epitope mapping and GST pulldown reactions, we have determined that amino acids in or near the lamin A tail domain (amino acids 369 to 519 and 490 to 660) are sufficient to interact with U L 31 protein.…”
Section: Discussionmentioning
confidence: 99%
“…High numbers of mutations in the tail domain have only been recorded in the lamins (200/232): lamins have several important functional motifs in their tail domains, including a nuclear localization signal (NLS), a region with immunoglobulin-like structure and a CaaX motif for membrane anchorage modifications. Sequence variation in the NLS results in aberrant filament assembly in the cytoplasm, and mutations affecting the Ig-like structure or the CaaX-dependent posttranslational processing have been directly associated with laminopathies [Krimm et al, 2002;Loewinger and McKeon, 1988].…”
Section: Analysis Of Datasetsmentioning
confidence: 99%
“…In addition, the mutations could disrupt interactions between the lamins and chromatin or other nuclear proteins. Indeed it has been suggested that mutations in the carboxy globular domain that cause FPLD and MAD are due to perturbations in the interactions between Lamin A and other proteins, such as the cholesterol synthesis regulator SREBP1 [36][37][38].…”
Section: ´3tmentioning
confidence: 99%